Twenty Years of Economics Curriculum: Trends, Issues, and Transformations?. Issue 3 (4th May 2019) - Adams, Erin C.
Abstract: This is a comprehensive review of literature related to K-12 economics curriculum spanning 20 years, from 1998-2018. The search for literature revealed 18 articles and book chapters in peer-reviewed journals and volumes related to social studies and economics education. The study revealed several trends and issues related to K-12 economics textbooks, including publishing trends, the extent to which economics curriculum is relevant and enactive, and the influence of neoclassical economic theory in serving as the "official knowledge" undergirding the curriculum. The review presents debates in the field related to these issues. The study also reveals the possible influence of the 2008 financial crisis, revealing that economics curriculum seems to have changed little, although the number of scholars critiquing the curriculum has risen dramatically.